2003
DOI: 10.1111/1469-8986.00083
|View full text |Cite
|
Sign up to set email alerts
|

Early posterior ERP components do not reflect the control of attentional shifts toward expected peripheral events

Abstract: Previous experiments investigating ERP correlates of anticipatory attention shifts triggered by central symbolic cues have identified a contralateral "early directing attention negativity," which was assumed to be generated by processes involved in the control of spatial orienting. Here we demonstrate that this component is not directly linked to the control of attentional shifts, but instead reflects the selection of task-relevant aspects of cue stimuli. In contrast, later ERP components triggered during cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
86
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 13 publications
18
86
0
Order By: Relevance
“…Based on careful observation of the current data and previous reports (Hietanen et al, 2008;Holmes et al, 2010;Van Velzen & Eimer, 2003), EDAN component was measured at posterior electrodes (averaged across P7 and PO7 on the left hemisphere and across P8 and PO8 on the right hemisphere) between 200 and 300 ms, while ADAN component was measured at anterior electrode sites (averaged across F5, F7, FC5, and FT7 for the left hemisphere and F6, F8, FC6, and FT8 for the right hemisphere) between 300 and 500 ms.…”
Section: Erpsmentioning
confidence: 78%
See 1 more Smart Citation
“…Based on careful observation of the current data and previous reports (Hietanen et al, 2008;Holmes et al, 2010;Van Velzen & Eimer, 2003), EDAN component was measured at posterior electrodes (averaged across P7 and PO7 on the left hemisphere and across P8 and PO8 on the right hemisphere) between 200 and 300 ms, while ADAN component was measured at anterior electrode sites (averaged across F5, F7, FC5, and FT7 for the left hemisphere and F6, F8, FC6, and FT8 for the right hemisphere) between 300 and 500 ms.…”
Section: Erpsmentioning
confidence: 78%
“…In arrow cuing studies, two components were shown to index two different attention stages (Nobre, Sebestyen, & Miniussi, 2000). The Early Directing Attention Negativity (EDAN) indexes the initial orienting of attention in the cued direction and reflects the increase of activity in cortical regions devoted to the processing of the cued location (Simpson et al, 2006) or the selection of aspects of the cue relevant for the accomplishment of the task (Van Velzen & Eimer, 2003). The Anterior Directing Attention Negativity (ADAN) indexes the holding of attention at the cued location and reflects the engagement of the fronto-parietal attention network in the control and redirection of attention in space (Praamstra, Boutsen, & Humphreys, 2005).…”
mentioning
confidence: 99%
“…This component has been shown to reflect the selection of targets among distractors in visual search tasks and has been localized to generators in extrastriate cortex, including V4 and posterior portions of inferior temporal cortex (Luck et al, 1997;Hopf et al, , 2002Hopf et al, , 2006. Moreover, it appears to be functionally equivalent to another component labeled EDAN ("early directing attention negativity") (Harter et al, 1989;Van Velzen and Eimer, 2003). At more frontal electrode sites, it is also possible that we would observe an anterior directing attention negativity (ADAN), which is a transient negative wave (350 -500 ms) that is thought to reflect control signals in prefrontal cortex involved in orienting attention toward the general location of an upcoming target (Harter et al, 1989;Nobre et al, 2000;Simpson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…First, we have shown that the posterior EDAN component reported in several earlier studies (cf. Harter et al, 1989;Hopf and Mangun, 2000) is not directly linked to the control of attentional shifts, but appears to reflect a lateralized visual response triggered by non-symmetrical visual cue stimulus (such as left-pointing and right-pointing arrows; see Van Velzen and Eimer, 2003, for more details). This component is absent in response to auditory attention cues , and when symmetrical visual cues are used , and the present experiment).…”
Section: Introductionmentioning
confidence: 99%